2000
DOI: 10.1177/030802260006300204
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Prescribed Adaptive Equipment: A Literature Review

Abstract: This article describes a literature review that examined the topic of the postdischarge compliance of individuals with prescribed adaptive equipment. Assisting individuals to accomplish tasks relevant to their activities of daily living and thereby achieve functional independence is central to the role of occupational therapy. The prescription of adaptive equipment is a frequently used intervention. The rationale for prescribing adaptive equipment is that it maximises a client's functional potential, allows fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 28 publications
3
51
0
2
Order By: Relevance
“…Non-use is deemed problematic because the patient does not receive the full benefit of the intervention [37]. However, the results of this study show that the ATD held meaning for the user even when the ATD was not used.…”
Section: Discussionmentioning
confidence: 73%
“…Non-use is deemed problematic because the patient does not receive the full benefit of the intervention [37]. However, the results of this study show that the ATD held meaning for the user even when the ATD was not used.…”
Section: Discussionmentioning
confidence: 73%
“…The current study found 70% of patients were using, but no longer required, adaptive equipment at week six post-operatively. Unlike the present study, the studies reviewed by Wielandt and Strong (2000) did not complete functional assessments with patients, which may explain the difference in utilisation rate of the studies. By completing a functional assessment at the week six follow up, the researcher was able to demonstrate to the patients that they were independent with the relevant area of function and they no longer required the adaptive equipment.…”
Section: How Long Do Patients Require Adaptive Equipment Following Tomentioning
confidence: 75%
“…However, there is little research which looks at patients' compliance and use of the equipment once it has been issued and patients are discharged home. From the results of their literature review Wielandt and Strong (2000) reported that, following discharge from orthopaedics, use of equipment at six weeks post-operatively was 46%. Reasons for stopping use of the equipment were put down to the patients physical health improving and 'living arrangements', however, the term 'living arrangements' was not explained further.…”
Section: Occupational Therapy and Adaptive Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The term 'prescription', commonly used to describe an assistive solution recommended to a consumer by a professional, is a symbol of entrenched and legitimised professional power in these approaches [27,28]. Clinical approaches are associated with practitioner expertise, objective measurement, and expectations of patient compliance with prescribed AT devices [29,30]. A key limitation of clinical approaches is that assistive solutions that work in a clinical environment are often difficult to integrate into the environments of their intended use [31].…”
Section: User-centred At Provisionmentioning
confidence: 99%